Preparation method of bionic microfluidic device for researching fluid migration in carbonate rock micro-nano cracks
Through the design and manufacturing of bionic microfluidic devices, the random forest algorithm and soft lithography technology are used to reproduce the fracture structure of carbonate rocks, and to form consistent surface properties through in-situ mineral growth, which solves the difficulty of accurately studying carbon with existing technologies. The problem of fluid migration in micro-nano cracks in acid rock has enabled in-depth research on the fluid-mineral coupling effect.
Patent Information
- Application Number
- CN202411766100.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing technology is difficult to accurately characterize the fluid migration process in carbonate micro-nano fractures. Traditional research methods such as core experiments and nuclear magnetic resonance technology are difficult to fully reflect the complexity in the actual underground reservoir environment due to the limitations of time and spatial resolution. sex.
Design a bionic microfluidic device, analyze carbonate core images through random forest algorithm, generate chip design drawings, use soft photolithography technology to reproduce the fracture structure, and use calcite nanocrystal seeds to grow in situ minerals to form carbon Consistent structure of salt rock fractures.
It achieves the maximum restoration of the fracture structure and surface physical and chemical properties of carbonate rocks, making the fracture structure and surface properties in the chip consistent with underground carbonate rocks, supporting in-depth research on fluid-mineral coupling effects.
Smart Images

Figure CN119334994A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microfluidic chip manufacturing technology and fluid migration research in carbonate rock fractures, and specifically relates to a preparation method of a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks. Background Art
[0002] Carbonate rock fractures are an important topic in the study of oil and gas migration and reservoir transformation. Traditional research methods such as core experiments and nuclear magnetic resonance (NMR) technology are difficult to accurately characterize the fluid migration process in micro-nano fractures due to their limited time and spatial resolution. In addition, existing microfluidic chips are usually manufactured through regular geometric structure processing methods. Their fracture morphology and surface physical and chemical properties are significantly different from those of real carbonate rock fractures, making it difficult to fully reflect the complexity of the actual underground reservoir environment.
[0003] In order to solve the above problems, a bionic microfluidic device that can highly restore the fracture morphology and surface physical and chemical properties of carbonate rocks is designed, which is of great significance for exploring complex physical fields, chemical fields and fluid-mineral coupling research. Summary of the invention
[0004] The present invention provides a method for preparing a bionic microfluidic device, which can truly replicate the fracture structure and surface physical and chemical properties of natural carbonate rocks.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks comprises the following steps:
[0007] Step 1: Analyze and classify the scanning electron microscope images of carbonate rock core slices using the random forest algorithm to generate chip design drawings;
[0008] Step 2: Based on the chip design drawings, the crack structure is replicated by using a photoresist template and polydimethylsiloxane using soft lithography technology, and bonded to a glass substrate to form a microfluidic chip;
[0009] Step 3: injecting a precursor liquid containing calcite nanocrystal seeds into the flow channel of the microfluidic chip, fixing the seeds by ultraviolet light irradiation, and realizing calcium carbonate mineral precipitation by injecting a saturated equilibrium solution to form a bionic microfluidic device.
[0010] Furthermore, the step 1 is specifically as follows:
[0011] Thin sections were cut from carbonate cores, vacuumed and sprayed with conductive carbon film, and the fractures and mineral composition were analyzed using scanning electron microscopy and energy dispersive X-ray spectroscopy to confirm the parent rock type and mineral distribution;
[0012] The crack boundary is smoothed and its definition is enhanced by using a Gaussian filter, and the preliminary outline of the crack is extracted using a two-dimensional Gaussian curvature matrix;
[0013] Mark the fractures and surrounding mineral types and pore characteristics to construct a training set for the random forest algorithm;
[0014] The image pixels are classified through the random forest algorithm to achieve semantic segmentation of minerals, fractures and pores, and the training parameters are dynamically adjusted to improve the classification accuracy and form mineral and fracture distribution data.
[0015] Extract the main boundaries and multi-scale features of the cracks and generate chip design drawings.
[0016] Furthermore, the step 2 is specifically as follows:
[0017] Prepare SU-8 photoresist template, and form crack structure mold through coating, exposure, development and hardening processes;
[0018] Component A (prepolymer) and component B (crosslinking agent) of polydimethylsilane (PDMS) were mixed in a mass ratio of 10:1, poured into a mold, evacuated and heated for curing;
[0019] The solidified PDMS and the glass to be bonded surface are plasma treated in a cleaning machine and then bonded together after plasma cleaning to form a microfluidic chip.
[0020] Furthermore, the preparation of the SU-8 photoresist template to form a crack structure mold through coating, exposure, development and hardening processes is specifically as follows:
[0021] Spinning: After cleaning and drying the silicon wafer, apply SU-8 photoresist at low and high speeds in a spinner and let it stand for 5 minutes;
[0022] Soft baking: Place the silicon wafer after coating on a leveled heating table, heat it at 65°C for 2 minutes, then heat it at 95°C for 10 minutes, and then cool it down to room temperature;
[0023] Exposure: Put the mask and the soft-baked silicon wafer together, and expose them with 365nm ultraviolet light for 75 seconds to cure the photoresist;
[0024] Post-baking: Separate the exposed silicon wafer and mask, and heat them again at 65°C for 2 minutes using a hot plate, then heat them at 95°C for 10 minutes, and then cool the exposed silicon wafer to room temperature along with the hot plate;
[0025] Development: Use developer to dissolve the unexposed areas, and then blow dry the silicon wafer with nitrogen after cleaning;
[0026] Hard baking: The developed silicon wafer is heated at 95°C for 5 minutes using a heating plate, then heated at 175°C for 20 minutes, and heated at 65°C for 5 minutes and cooled to room temperature to form a crack structure mold.
[0027] Furthermore, the step three is specifically as follows:
[0028] Injecting sodium hydroxide solution into the flow channel of the microfluidic chip to clean the channel surface, and performing silanization treatment with 3-propyl acrylate;
[0029] A pre-liquid containing calcite nanocrystal seeds is injected into the flow channel of the microfluidic chip after silanization, and the seeds are fixed on the crack surface by ultraviolet light irradiation;
[0030] A mixed solution of sodium bicarbonate solution and calcium chloride solution is injected to precipitate calcium carbonate minerals and optimize the physical and chemical properties of the fracture surface.
[0031] Furthermore, the preparation method of the pre-fluid is:
[0032] 5 mg of calcite seed crystals, 20 μL of polyethylene glycol diacrylate, 5 μL of photoinitiator, 40 μL of polyethylene glycol, 2 μL of acrylic acid, and 33 μL of deionized water were uniformly mixed and dispersed by ultrasonic vibration to form a uniform solution.
[0033] Furthermore, the sodium bicarbonate solution and the calcium chloride solution are mixed in a ratio of 1:2.84 to obtain a balanced solution with a saturation of 1.
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] The present invention can be used for the coupling study of all fluids and carbonate rock fractures, and provides a method for restoring the carbonate rock fracture structure to the greatest extent and a method for cloning the rock surface properties, so that the fractures in the chip are consistent with the underground carbonate rock fracture structure in terms of structure and surface physical and chemical properties, and the surface properties of the flow channel are controlled according to the different mineral growth modes. By marking a small number of mineral pores and incorporating them into the random forest model for the classification and extraction of pore structures that are difficult to distinguish, the extracted fracture structure is replicated using soft lithography technology to form a structure consistent with the carbonate rock fracture microchannel.
[0036] The present invention adopts the in-situ mineral growth method of calcite nanocrystal seeds. This method can produce a micro-model with dynamically adjustable pore structure and surface minerals, which is convenient for carrying out control experiments and deeply exploring the fluid-mineral coupling effect, such as the fractionation of condensate oil in fracture migration, acid fracturing of formations, CCUS sealing effect, etc. It is not only economical and convenient, but also has huge expandability and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the description and claims, serve to illustrate the embodiments of the invention. Where appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.
[0038] Figure 1 A schematic diagram of a chip design drawing of the present invention is shown;
[0039] Figure 2 The schematic diagram of the experimental device of the present invention is shown; wherein, 1-air compressor, 2-constant pressure pump, 3-microscope, 4-microfluidic chip, 5-heating module, 6-centrifuge tube, 7-computer;
[0040] Figure 3 The structure diagram of the bionic chip after completion of the present invention is shown. DETAILED DESCRIPTION
[0041] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0042] The embodiment of the present invention mainly includes three parts: the first part is to extract the structure of carbonate rock fractures. The second part is to form a drawing and make a mask according to the extracted fracture structure, and then use a soft lithography method to prepare a microfluidic basic chip with a fracture structure. The third part is to grow mineral surface on the flow channel.
[0043] Part I: Natural fracture structure extraction
[0044] A thin rock slice with a side length of 1.5cm*3cm and a thickness of 1.5mm was cut from the carbonate core. After vacuum carbon injection, SEM-EDS was used to confirm that the parent rock of the fracture was carbonate rock again, and the mineral distribution characteristics around the fracture were obtained. In order to obtain multi-scale fracture network images, 54 regional SEM images of the rock slice were obtained for large-scale splicing.
[0045] Then, the minerals, organic matter, intergranular pores, intragranular dissolution pores, microcracks and large cracks in the SEM images of the large thin sections of the rock were manually marked to establish a training set for the random forest algorithm. Finally, it was expanded to classify the pore structure characteristics of the entire image. The detailed process is:
[0046] Step 1: Gaussian image processing
[0047] Because the spatial distribution of carbonate minerals, organic matter, and pores / fractures is highly heterogeneous, images processed by convolution Gaussian functions with different filters can make the blurred pixel boundaries of carbonate fractures clear. The mean of the Gaussian distribution of two adjacent positions is expressed by σ, and σ is selected as 10.
[0048] Step 2: Select edge segmentation method.
[0049] Segment image edges using Hessian ofGaussian Eigenvalues in 2D.
[0050] Step 3: Labeling minerals and pore types for training classifiers
[0051] According to the development characteristics of carbonate rock minerals and fracture systems, the minerals mainly include dolomite, calcite, feldspar, and quartz, and the pore-fracture system mainly includes mineral intergranular pores, mineral intragranular dissolution pores, micron-scale fractures, and centimeter-scale fractures. They are marked on the image for the random forest training set.
[0052] Step 4: Interactive training
[0053] The pixel features of semantic segmentation are used as the basis for random forest classification of all pixels, and the training library of semantic segmentation is continuously supplemented according to the prediction results. Finally, the maximum probability plane distribution of different types of minerals, pores and cracks is formed.
[0054] Step 5: Create a chip drawing
[0055] Considering that the largest fracture contains multi-scale structural information and has a major contribution to seepage, a chip design diagram is formed for the identification of the main fracture boundary. In order to facilitate the comparison with the actual core seepage in the later stage, the largest chip is 1:1 with the fracture, and the internal depth is 9μm. Figure 1 shown.
[0056] Part 2: Complete the basic chip structure manufacturing
[0057] The microfluidic chip processing method is a soft lithography technology. The chip processing process of the present invention is described in detail below.
[0058] The specific process of soft lithography technology includes eight steps.
[0059] Step 1: Coating: Use isopropyl alcohol and deionized water to clean the polished side of the silicon wafer respectively, use clean gas to blow dry the surface, and use a heating table to dry the silicon wafer to remove moisture from the silicon wafer and ensure that the silicon wafer is clean and dry.
[0060] Place a clean silicon wafer in the center of the coating machine tray, turn on the coating machine vacuum pump, make sure the coating machine tray sucks the silicon wafer tightly, carefully pour SU-82035 photoresist on the center of the silicon wafer, cover the coating machine lid, start the coating machine, set the coating machine to two speeds, low speed 500rpm / s, time: 10s; high speed 2500rpm / s, time 30s, when the coating machine stops running, let it stand for 5 minutes.
[0061] The pattern of the prepared chip is mainly determined by the pattern of the mask. Compared with the traditional regular chip, this chip captures the real core fractures and realizes the flow state of crude oil in the core.
[0062] Step 2: Soft Bake: Place the silicon wafer after the coating is applied on a leveled heating platform, heat it at 65°C for 2 minutes, then adjust the temperature of the heating platform to 95°C and heat it for 10 minutes. Then the temperature is lowered to room temperature along the heating plate.
[0063] Step 3: Exposure: Turn on the UV exposure machine and let it work for a while. When the UV exposure energy is stable, use a joule meter to measure the UV energy to make its energy value consistent with the required exposure energy. Put the mask and the soft-baked silicon wafer together for exposure. After testing, use a UV exposure machine with a wavelength of 365nm for 75s.
[0064] Step 4: Post Exposure Bake: Carefully separate the exposed silicon wafer and the mask, and use a heating plate to heat the silicon wafer again. The heating temperature and time are: 65℃ for 2min, 95℃ for 10min, and then the exposed silicon wafer is cooled to room temperature along with the heating plate.
[0065] Step 5: Development: Use developer (PGMEA) to develop the post-baked silicon wafer, and alternately clean it with isopropyl alcohol and deionized water to clean the unexposed photoresist from the silicon wafer. Finally, use deionized water to clean it and use clean nitrogen to blow away the remaining moisture on the silicon wafer.
[0066] Step 6: Hard Bake: After cleaning, the template needs to be hard baked. First, heat it at 95°C for 5 minutes using a heating plate, then heat it at 175°C for 20 minutes, and then heat it at 65°C for 5 minutes and cool it to room temperature.
[0067] Step 7: Mix component A (prepolymer) and component B (cross-linking agent) of PDMS in a mass ratio of 10:1, and use a stirring rod to stir them thoroughly to make them fully mixed. The fully mixed PDMS is filled with tiny bubbles. Finally, use a vacuum kettle to evacuate the bubbles in the PDMS.
[0068] Place the SU-8 template in a culture dish, pour the mixed PDMS with bubbles fully removed onto the SU-8 template, and put it into a vacuum oven for evacuation for 10 minutes. Place the culture dish on a heating plate and heat it at 65°C for 4 hours. After the PDMS solidifies, use a scalpel to cut the PDMS along the edge of the chip, and use a 5mm puncher to punch holes at the inlet and outlet of the chip.
[0069] Step 8: Bonding: Clean the channel surface and the glass surface to be bonded with dust-free tape, and place them in a plasma cleaner for plasma treatment. After treatment, gently bond the PDMS and glass together to complete the bonding.
[0070] Step 9: In order to improve the connection strength of the pipeline on the chip, silicone rubber is used to process the inlet and outlet of the flow channel after bonding to facilitate the pipeline connection of the subsequent experimental device.
[0071] Part 3: In-situ growth of minerals in the flow channels of the chip
[0072] Step 1: Build the experimental device. The schematic diagram of the experimental device is as follows Figure 2 As shown: It mainly includes pressure controller, flow sensor, microscope, microfluidic chip, heating module, etc. The fluid is driven by the pressure controller, the fluid flow process is observed in real time by the microscope, and the heating module is controlled to realize the temperature control of the chip.
[0073] The experimental device is attached. Figure 2 .
[0074] Step 2: Channel surface functionalization.
[0075] First, a 1 mol / L sodium hydroxide solution was injected into the prefabricated base chip using a constant pressure pump of 150 mbar and a syringe pump and allowed to remain there for 1 hour to clean the inside of the chip.
[0076] The channels were then rinsed with deionized water to ensure that the residual sodium hydroxide solution was removed. 3-(Trimethoxysilyl)propyl acrylate was then injected into the microchannels for 5 minutes to react, so that the glass surface was functionalized by the silane surface with propyl acrylate groups, and the free radical polymer groups were grafted onto the silica surface.
[0077] Finally, the channels were thoroughly rinsed with ethanol and deionized water to remove unreacted silane reagents and ensure the effectiveness of surface functionalization.
[0078] Step 3:
[0079] After channel functionalization and drying, the pre-liquid was injected into the microchannel and kept for 1 h to prepare for the photo-initiated carboxylic acid free radical polymerization.
[0080] The method for preparing the pre-liquid is as follows: 5 mg of calcite seeds, 20 μL of polyethylene glycol diacrylate, 5 μL of photoinitiator, 40 μL of polyethylene glycol (Mn≈4000, 50% solution), 2 μL of acrylic acid, and 33 μL of deionized water are ultrasonically shaken for 8 hours to fully disperse the calcite nano-seeds.
[0081] Then, the nanocrystals were irradiated with 365 nm ultraviolet light for 1 min. UV exposure fixed the nanocrystals on the inner surface of the microchannel and generated polar carboxylic acid groups, which are very easy to fix Ca 2+ and CO3 2- .
[0082] Finally, the microchannels were rinsed with deionized water to remove the uncured precursor solution.
[0083] Considering that mineral growth is affected by temperature, the growth temperature of calcium carbonate mineral in this experiment was set to 25°C, and the temperature was controlled by a temperature-controlled heating pad and an infrared temperature detector. The solubility of calcium carbonate at 25°C is 6.1×10 -5 M, so 0.88mol / L sodium bicarbonate solution and 2.5mol / L calcium chloride solution were mixed at a ratio of 1:2.84 to obtain a balanced solution with a saturation of 1. The balanced solution was injected into the previous chip at a rate of 0.1mL / min, and the injection was repeated every 2 minutes for a total of 3 times.
[0084] The inside of the manufactured bionic chip Figure 3 .
[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks, characterized in that: The following steps are involved: Step 1: Analyze and classify the scanning electron microscope images of carbonate rock core slices using the random forest algorithm to generate chip design drawings; Step 2: Based on the chip design drawings, the crack structure is replicated by using a photoresist template and polydimethylsiloxane using soft lithography technology, and then bonded to a glass substrate to form a microfluidic chip; Step 3: injecting a precursor liquid containing calcite nanocrystal seeds into the flow channel of the microfluidic chip, fixing the seeds by ultraviolet light irradiation, and realizing calcium carbonate mineral precipitation by injecting a saturated equilibrium solution to form a bionic microfluidic device.
2. The method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks according to claim 1, characterized in that: The step 1 is specifically as follows: Thin sections were cut from carbonate cores, vacuumed and sprayed with conductive carbon film, and the fractures and mineral composition were analyzed using scanning electron microscopy and energy dispersive X-ray spectroscopy to confirm the parent rock type and mineral distribution; The crack boundary is smoothed and its definition is enhanced by using Gaussian filter, and the preliminary outline of the crack is extracted using two-dimensional Gaussian curvature matrix; Mark the fractures and surrounding mineral types and pore characteristics to construct a training set for the random forest algorithm; The image pixels are classified through the random forest algorithm to achieve semantic segmentation of minerals, fractures and pores, and the training parameters are dynamically adjusted to improve the classification accuracy and form mineral and fracture distribution data. The main boundaries and multi-scale features of the cracks are extracted to generate chip design drawings.
3. The method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks according to claim 1, characterized in that: The step 2 is specifically as follows: Prepare SU-8 photoresist template, and form crack structure mold through coating, exposure, development and hardening processes; The prepolymer of polydimethylsilane and the crosslinking agent are mixed in a mass ratio of 10:1, poured into a mold, evacuated and heated for curing; The solidified polydimethylsilane and the glass surface to be bonded are subjected to plasma treatment in a cleaning machine and then bonded together after plasma cleaning to form a microfluidic chip.
4. The method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks according to claim 3, characterized in that: The preparation of the SU-8 photoresist template to form a crack structure mold through coating, exposure, development and hardening processes is specifically as follows: Spinning: After cleaning and drying the silicon wafer, apply SU-8 photoresist at low and high speeds in a spinner and let it stand for 5 minutes; Soft baking: Place the silicon wafer after coating on a leveled heating table, heat it at 65°C for 2 minutes, then heat it at 95°C for 10 minutes, and then cool it down to room temperature; Exposure: Put the mask and the soft-baked silicon wafer together, and expose them with 365nm ultraviolet light for 75 seconds to cure the photoresist; Post-baking: Separate the exposed silicon wafer and mask, and heat them again at 65°C for 2 minutes using a hot plate, then heat them at 95°C for 10 minutes, and then cool the exposed silicon wafer to room temperature along with the hot plate; Development: Use developer to dissolve the unexposed areas, and blow dry the silicon wafer with nitrogen after cleaning; Hard baking: The developed silicon wafer is heated at 95°C for 5 minutes using a heating plate, then heated at 175°C for 20 minutes, and heated at 65°C for 5 minutes and cooled to room temperature to form a crack structure mold.
5. The method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks according to claim 1, characterized in that: The step three is specifically as follows: Injecting sodium hydroxide solution into the flow channel of the microfluidic chip to clean the channel surface, and performing silanization treatment with 3-propyl acrylate; A pre-liquid containing calcite nanocrystal seeds is injected into the flow channel of the microfluidic chip after silanization, and the seeds are fixed on the crack surface by ultraviolet light irradiation; A mixed solution of sodium bicarbonate solution and calcium chloride solution is injected to precipitate calcium carbonate minerals and optimize the physical and chemical properties of the fracture surface.
6. The method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks according to claim 3, characterized in that: The preparation method of the pre-fluid is: 5 mg of calcite seed crystals, 20 μL of polyethylene glycol diacrylate, 5 μL of photoinitiator, 40 μL of polyethylene glycol, 2 μL of acrylic acid, and 33 μL of deionized water were uniformly mixed and dispersed by ultrasonic vibration to form a uniform solution.
7. The method for preparing a bionic microfluidic device for studying fluid migration in micro-nano fractures of carbonate rocks according to claim 6, characterized in that: The sodium bicarbonate solution and the calcium chloride solution are mixed in a ratio of 1:2.84 to obtain a balanced solution with a saturation of 1.
Citation Information
Patent Citations
Submicron spherical biological calcium carbonate as well as preparation method and application thereof
CN111792661A
Shale SEM image segmentation method based on machine learning
CN112348831A
Carbonate reservoir microcosmic model, and preparation method and application thereof
CN112598986A
Micro-fluidic chip for research on oil-water seepage mechanism of carbonate reservoir and manufacturing method of micro-fluidic chip
CN116920971A
Manufacturing method of triple medium type carbonate reservoir micro-nano fluidic model
CN118210077A
Cited By
Carbon dioxide salt crystallization observation system and method
CN120161042A
A carbon dioxide salt crystallization observation system and method
CN120161042B
Gas-water-rock reaction and particle corrosion-migration in-situ visual quantitative determination method and device based on micro-fluidic chip
CN121577839A
A microfluidic chip-based gas-water-rock reaction and particle dissolution-migration in-situ visualization and quantitative determination method and device
CN121577839B